Effect of Technological Additions to Chocolate Mass Quality - qizi, Saidnazarova Irodakxon Saidnazar; Rasulovich, Mardonov Ne`matilla; Sabirzhanovna, Faizieva Nargiza (European Journal of Life Safety and Stability (2660-9630), 2022)
Currently, there are possibilities for falsification of chocolate mass making, associated on the one hand with the replacement of raw materials, and on the other hand with a violation of technological processes in production. Therefore, it is necessary to improve the quality control system of incoming raw materials and the production technology.